(untitled) (Muitas Vozes, 2021)
This study aimed to investigate the figuration of the character Lolita, in Nabokov’s novel, as well as in four of its covers. Characters have long been the object of study in the literary sphere; however, there has been a transcendence of them for other media, including on book covers, which has aroused interest in broader studies. The cover, in addition to the book’s paratext, is widely used by the publishing market as marketing for the work. In many cases, these two functions collide. The hypothesis in this text is that the advertising aspects of the work end up becoming so important that publishers often favor some elements of the novel over others, such as the femme fatale and the nymphet. As a basis for the analysis, the studies conducted by Reis (2014), Eder, Jannidis and Schneider (2010) and Sonzogni (2011) were used.